FOREST Unbiased Galactic Plane Imaging Survey with the Nobeyama 45 m telescope (FUGIN). IV. Galactic shock wave and molecular bow shock in the 4 kpc arm of the Galaxy. (13th September 2018) - Sofue, Yoshiaki; Kohno, Mikito; Torii, Kazufumi; Umemoto, Tomofumi; Kuno, Nario; Tachihara, Kengo; Minamidani, Tetsuhiro; Fujita, Shinji; Matsuo, Mitsuhiro; Nishimura, Atsushi; Tsuda, Yuya; Seta, Masumichi
Abstract: The FUGIN CO survey revealed the three-dimensional structure of a galactic shock wave in the tangential direction of the 4 kpc molecular arm. The shock front is located at G30.5+00.0 + 95 km s −1 on the upstream (lower longitude) side of the star-forming complex W 43 (G30.8−0.03), and comprises a molecular bow shock (MBS) concave to W 43, exhibiting an arc-shaped molecular ridge perpendicular to the galactic plane with width ∼0${^{°}_{.}}$ 1(10 pc) and vertical length ∼1° (100 pc). The MBS is coincident with the radio continuum bow of thermal origin, indicating association of ionized gas and similarity to a cometary bright-rimmed cloud. The upstream edge of the bow is sharp, with a growth width of ∼0.5 pc indicative of the shock front property. The velocity width is ∼10 km s −1, and the center velocity decreases by ∼15 km s −1 from the bottom to the top of the bow. The total mass of molecular gas in the MBS is estimated to be ∼1.2 × 10 6 M ⊙, and ionized gas ∼2 × 10 4 M ⊙ . The vertical disk thickness has a step-like increase at the MBS by ∼2 times from lower to upper longitudes, which indicates hydraulic jump in the gaseous disk. We argue that the MBS was formed by the galactic shock compression of an accelerated flow in the spiral-arm potential encountering the W 43 molecular complex. A bow-shock theory can reproduce the bow morphology well. We argue that molecular bows are common in galactic shock waves, not only in the Galaxy but also in galaxies, where MBSs are associated with giant cometary H ii regions. We also analyzed the H i data in the same region to obtain a map of H i optical depth and molecular fraction. We found firm evidence of the H i to H2 transition in the galactic shock as revealed by a sharp molecular front at the MBS front.